1993
DOI: 10.1111/j.1432-1033.1993.tb17637.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Crabtree effect and an endogenous fuel in the energy metabolism of resting and proliferating thymocytes

Abstract: Rat thymocytes have been used to characterize the changes in energy metabolism that occur as cells undergo a resting/proliferation transition. In the resting state, anaerobic ATP production accounts for only 4% of ATP turnover. The remainder is fueled by the oxidation of a mixture of an unidentified endogenous fuel (62%), glucose (18%) and glutamine (16%). 48 h after mitogen stimulation, the ATP turnover has increased twofold. In these proliferating cells, glucose inhibits oxygen consumption by 58%, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(120 citation statements)
references
References 33 publications
3
117
0
Order By: Relevance
“…Nevertheless, Crabtree suggested already in 1929 that exacerbated glycolytic activity hampered respiration, not only in tumors but also in other mitotically active tissues. The inhibition of oxygen consumption by glucose in proliferating cells was then named the Crabtree effect (Guppy et al, 1993). Decades later, Weinhouse (1972) observed that tumor cells possess fetal isoforms of some glycolytic enzymes, suggesting this could be responsible for their increased glycolytic flux.…”
Section: The Warburg Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Crabtree suggested already in 1929 that exacerbated glycolytic activity hampered respiration, not only in tumors but also in other mitotically active tissues. The inhibition of oxygen consumption by glucose in proliferating cells was then named the Crabtree effect (Guppy et al, 1993). Decades later, Weinhouse (1972) observed that tumor cells possess fetal isoforms of some glycolytic enzymes, suggesting this could be responsible for their increased glycolytic flux.…”
Section: The Warburg Effectmentioning
confidence: 99%
“…Glucose levels in blood are exquisitely maintained at approximately 5 mM under physiological conditions (Rodgers et al, 2005). Remarkably, this substrate represents the major energy (Guppy et al, 1993) and carbon source of proliferating cells; glucose deprivation can induce cellcycle arrest (Holley and Kiernan, 1974) and death (Ahmad et al, 2005). Thus, variations in glucose availability/utilization arising within specific cell niches generate clonal selection pressures.…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Cell proliferation is a process that consumes a great deal of energy with a 2-4-fold increase over nonproliferating cells (87)(88)(89). Therefore, the inhibition of cell proliferation under glucose starvation saves energy, and all of the ATP produced by glycolysis is used for the survival of the cells.…”
Section: Comparison Of Metabolism Between Mcf-7 and Mda-mb-453mentioning
confidence: 99%
“…Oxygen consumption was not measured and would almost certainly demonstrate the oxidation of other fuels. Similarly it is now obvious that aerobic glycolysis contributes significantly (20 -50%) to ATP production under aerobic conditions in a variety of cell types (reviewed in Neermann and Wagner, 1996;Guppy et al, 1993) so lactate production must be measured if one is to get a meaningful measure of total ATP turnover.…”
mentioning
confidence: 99%